2021
DOI: 10.1002/ctpp.202000176
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a test charge in a free‐electron gas at warm dense matter and dense non‐ideal plasma conditions

Abstract: The screening of a test charge by partially degenerate non‐ideal free electrons at conditions related to warm dense matter and dense plasmas is investigated using linear response theory and the local field correction based on ab initio Quantum Monte‐Carlo simulations data. The analysis of the obtained results is performed by comparing to the random phase approximation and the Singwi–Tosi–Land–Sjölander approximation. The applicability of the long‐wavelength approximation for the description of screening is inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In our analysis, we consider the densities r s = 2 and r s = 6 and a temperature T = T F , where r s = a/a B defines the number density of electrons which is given as the ratio between the Wigner-Seitz radius a and the first Bohr radius a B . At T T F , the parameter r s also characterizes electronic non-ideality 81,82 . Therefore, it is used also as a coupling parameter.…”
Section: Theory and Simulation Methodsmentioning
confidence: 99%
“…In our analysis, we consider the densities r s = 2 and r s = 6 and a temperature T = T F , where r s = a/a B defines the number density of electrons which is given as the ratio between the Wigner-Seitz radius a and the first Bohr radius a B . At T T F , the parameter r s also characterizes electronic non-ideality 81,82 . Therefore, it is used also as a coupling parameter.…”
Section: Theory and Simulation Methodsmentioning
confidence: 99%
“… 41 , 42 Additionally, nonlinear density response functions can extend quantum fluid models (quantum hydrodynamics and time-dependent OF-DFT) beyond the weak perturbation regime. 43 48 Moreover, static nonlinear density response functions are needed for the systematic improvement of effective pair interaction models for WDM 49 52 and liquid metals. 53 55 Finally, Moldabekov and co-workers 56 , 57 have recently suggested to deliberately probe the nonlinear regime in X-ray Thomson scattering experiments 58 as an improved method for the inference of plasma parameters such as the electronic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the parameter range corresponding to densities r s ≳ 2 and temperatures 0.01 ≲θ < 1 is highly important for numerous applications. Recently, it was shown that the static nonlinear density response functions of the electron gas can be used for the construction of advanced kinetic energy functionals required for orbital-free density functional theory (OF-DFT)-based simulations , with applications at ambient and extreme conditions. , Additionally, nonlinear density response functions can extend quantum fluid models (quantum hydrodynamics and time-dependent OF-DFT) beyond the weak perturbation regime. Moreover, static nonlinear density response functions are needed for the systematic improvement of effective pair interaction models for WDM and liquid metals. Finally, Moldabekov and co-workers , have recently suggested to deliberately probe the nonlinear regime in X-ray Thomson scattering experiments as an improved method for the inference of plasma parameters such as the electronic temperature. However, these applications remain in their infancy since the NLRT of correlated electrons is significantly less developed compared to the LRT .…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Additionally, non-linear density response functions can extend quantum fluid models (quantum hydrodynamics and time-dependent orbital-free density functional theory) beyond the weak perturbation regime. [43][44][45][46][47][48] Moreover, static non-linear density response functions are needed for the systematic improvement of effective pair interaction models for WDM [49][50][51][52] and liquid metals. [53][54][55] Finally, Moldabekov and co-workers 56,57 have recently suggested to deliberately probe the nonlinear regime in X-ray Thomson scattering experiments 58 as an improved method for the inference of plasma parameters such as the electronic temperature.…”
Section: Introductionmentioning
confidence: 99%